Association of elevated hs-CRP and multiple infarctions with outcomes of minor stroke or TIA: subgroup analysis of CHANCE randomised clinical trial. Issue 1 (21st September 2020) - Wang, Guangyao; Jing, Jing; Li, Jiejie; Pan, Yuesong; Yan, Hongyi; Meng, Xia; Zhao, Xingquan; Liu, Liping; Li, Hao; Wang, David Z; Wang, Yongjun; Wang, Yilong
Abstract : Background and purpose: The relationship of high-sensitive C-reactive protein (hs-CRP) levels and infarction numbers with the prognosis of stroke is uncertain. This study evaluated the association of different hs-CRP levels and infarction numbers with the prognosis of acute minor ischaemic stroke or transient ischaemic attack (TIA). Methods: A subset of 807 patients with both hs-CRP measurement and baseline MRI was included from the Clopidogrel in High-risk Patients with Acute Non-disabling Cerebrovascular Events trial. The primary efficacy outcome was the occurrence of an ischaemic stroke at the 1-year follow-up. Infarction numbers were classified as multiple acute infarctions (MAIs), single acute infarction and no acute infarction (NAI). The association between different hs-CRP levels with different infarction numbers and the risk of any outcome was analysed using multivariable Cox regression models. Results: Among the 807 patients, 84 (10.4%) patients had a recurrent ischaemic stroke within 1 year. After adjustment for conventional confounding factors, patients with both elevated hs-CRP levels and MAIs were associated with approximately 4.7-fold of risk of ischaemic stroke within 1 year (16.7% vs 3.5%, HR 4.68, 95% CI 1.54 to 14.23, p=0.007), compared with those with non-elevated hs-CRP levels and NAI. Similar results were observed for the composite events. Conclusions: Combined elevated hs-CRP levels and MAIs may increase 1-year stroke risk stratification efficiency in patients with minor ischaemic stroke or TIA compared with using those markers alone, which indicated that the combination of inflammatory and imaging markers might improve the effectiveness of risk stratification concerning minor ischaemic stroke or TIA. ClinicalTrials.gov Registry (NCT00979589 ).